Evaluasi Penggunaan Kuis Interaktif Sistem Reproduksi Terhadap Peningkatan Pengetahuan Mahasiswa Calon Peserta Ujian Kompetensi Mahasiswa Program Pendidikan Dokter (UKMPPD) - Winarto, Winarto; Firdaus, Firdaus; Nazriati, Elda; Aditama, Hanna Shafira (Fakultas Kedokteran Universitas Riau, 2025)
Interactive quizzes are one of the most widely developed forms of e-learning in education. As interactive multimedia, interactive quizzes can impact the field of education. This study aims to determine the increase in student knowledge before and after using interactive quizzes as a learning medium and to identify the qualitative advantages and disadvantages of using interactive quizzes. This research is a mixed-method sequential explanatory study involving 20 student respondents at the comprehensive station for March 2022, using a total sampling technique. This study uses pre-test and post-test measurements to assess knowledge improvement and interviews to determine user acceptance. Measuring the mean value of the pre-test, 53.5, and the post-test value of 75.2, with the Wilcoxon test obtained a sig. (2-tailed) of 0.000. Qualitative assessment of system, usage, and interaction aspects shows that this interactive quiz is easy to use, interesting, interactive, and valuable as a learning medium. The conclusion indicates that interactive quizzes are accepted as an independent learning medium and can increase the knowledge of their users.